Halomonas vilamensis sp. nov., isolated from high-altitude Andean lakes - Menes, Rodolfo Javier (2011)
A Gram-negative, aerobic, rod-shaped, non-spore-forming bacterium (SV325T) was isolated from the sediment of a hypersaline lake located at 4600 m above sea level (Laguna Vilama, Argentina). Strain SV325T formed cream-to-pink colonies, was motile and moderately halophilic, and grew at NaCl concentrations of 1-25 % (w/v) with an optimum at 5-10 % (w/v). Growth occurred at 5-40 degrees C (optimum around 30 degrees C) and at pH levels 5.0-10.0 (optimum 7.0-8.0). The bacteria does not produce exopolysaccharides, stained positively for intracellular polyphosphate granules but not for poly-beta-hydroxyalkanoates It produced catalase and oxidase, reduced nitrate to nitrite, hydrolyzed gelatin, did not produce acids from sugars, and utilized a limited range of substrates as carbon and energy sources: acetate, caproate, fumarate, DL-beta-hydroxybutyrate, malate, maleate, malonate and succinate. The predominant ubiquinones were Q-9 (92.5 %) and Q-8 (7.5 %), the major fatty acids were C19:0 cyclo omega8c, C16:0, C17:0 cyclo and C16:1 omega7c/15 iso 2-OH, and the DNA G+C content was 55.0 mol%. Phylogenetic analyses based on 16S rRNA gene indicated that strain SV325T belongs to the genus Halomonas in the class Gammaproteobacteria. Physiological and biochemical tests allowed phenotypic differentiation of strain SV325T from closely related, valid, published species names and therefore represents a new species; the name Halomonas vilamensis sp. nov. is proposed for this species, with type strain SV325T (=DSM 21020T =LMG 24332T).